Using Facebook as a Digital Platform During the Covid 19 Pandemic to Support Online Learning - Sri Supiah Cahyati; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2024)
Background. Covid-19 has become a pandemic declared by WHO (World Health Organization) since March 2020. This pandemic has rocked the whole world, including Indonesia. Covid-19 not only has an impact on the economic sector, but also has an impact on several aspects of society, especially in the educational environment. Purpose. The aim of this research is to discuss one familiar social media platform, namely Facebook, as a solution to overcome the dampening impact of Covid-19 on the learning environment. Method. This research uses quantitative methods using survey capital and in-depth surveys. The survey used in this research is online based. Results. The results of this research are how Facebook can be useful as a solution during the pandemic to help smooth online learning. Conclusion. The conclusion of this research explains that Facebook as a digital platform can be used to support online learning in the Covid-19 era, because it contains various features that can help students continue to carry out learning effectively even when online.